PENDIDIKAN KESEHATAN CTPS SEBAGAI PEMUTUS RANTAI KUMAN PENYEBAB INFEKSI DAN PENYAKIT - Tri Cahyadi, Anggih; Syafruddin; Abd Haris; Mirham Nurul Hairunis; Nurul Hairunis; Suriya Ningsyih; Hairunisa; Ihsan; Zuriatin; Sri Yanti (Politeknik Negeri Sriwijaya, 2023)
Health Education on the Steps of Handwashing with Soap (CTPS) plays a crucial role in breaking the chain of germ transmission that can cause infections and diseases, especially in the Elementary School environment. The aim of this service is to enhance children's knowledge and attitudes to correctly apply the steps of handwashing with soap (CTPS) in their daily lives, both within and outside the school environment. This activity is expected to prevent the risk of infections and diseases transmitted through contaminated objects, thereby improving the children's health status. The method used in carrying out community service activities is to convey information through a lecture method, namely a presentation combining educational games and ending with the practice of washing hands with soap (CTPS). The service was conducted at SDN 03 Wera on May 31, 2023. The outreach activities carried out received quite high enthusiasm where the students of SDN 03 Wera were very interested in discussing the benefits of CTPS health education. CTPS health education at SDN 3 Wera is an extraordinary step. This shows a commitment to not only providing information, but also creating an environment where healthy practices like CTPS become a natural part of children's daily routines.